Roles of type II H+-PPases and PPsPase1/PECP2 in early developmental stages and PPi homeostasis of Arabidopsis thaliana - Tojo, Hiroshi; Tabeta, Hiromitsu; Gunji, Shizuka; Hirai, Masami Y.; David, Pascale; Javot, Hélène; Ferjani, Ali (Frontiers in Plant Science, 2023)
The regulation of intracellular pyrophosphate (PPi) level is crucial for proper morphogenesis across all taxonomic kingdoms. PPi is released as a byproduct from ~200 metabolic reactions, then hydrolyzed by either membrane-bound (H+-PPase) or soluble pyrophosphatases (PPases). In Arabidopsis, the loss of the vacuolar H+-PPase/FUGU5, a key enzyme in PPi homeostasis, results in delayed growth and a number of developmental defects, pointing to the importance of PPi homeostasis in plant morphogenesis. The Arabidopsis genome encodes several PPases in addition to FUGU5, such as PPsPase1/PECP2, VHP2;1 and VHP2;2, although their significance regarding PPi homeostasis remains elusive. Here, to assess their contribution, phenotypic analyses of cotyledon aspect ratio, palisade tissue cellular phenotypes, adaxial side pavement cell complexity, stomatal distribution, and etiolated seedling length were performed, provided that they were altered due to excess PPi in a fugu5 mutant background. Overall, our analyses revealed that the above five traits were unaffected in ppspase1/pecp2, vhp2;1 and vhp2;2 loss-of-function mutants, as well as in fugu5 mutant lines constitutively overexpressing PPsPase1/PECP2. Furthermore, metabolomics revealed that ppspase1/pecp2, vhp2;1 and vhp2;2 etiolated seedlings exhibited metabolic profiles comparable to the wild type. Together, these results indicate that the contribution of PPsPase1/PECP2, VHP2;1 and VHP2;2 to PPi levels is negligible in comparison to FUGU5 in the early stages of seedling development.